(untitled) (مجلة ديالى للبحوث الانسانية, 2023)
Abstract It is safe to say that the linguistics revolution has begun and the revolution is being computerized. It is no amplification to say that linguistics has undergone a renaissance with the rapid development of computers and the internet that are witnessing in the modern era through the spread and tremendous changes brought about by digital technology through computing, which marked the beginning of an information age. For the time being, the field of computational linguistics straddles linguistics and computer science with the help of psychology and logic by using computers to simplify the handling of linguistic issues. It is considered as a branch of computer science and linguistics. However, it is built on the collaboration between computer science and linguistics. Every aspect of linguistics has been affected by the application of this technology. The aim of this review is to focus on the field of computational linguistics and its skills by focusing on linguistics with reference to the uses of computers in relation to teaching and the role of teachers today towards students